Expression of cytokine and extracellular matrix mRNAs in fetal hepatic stellate cells. (4th August 2017) - Tan, Keai Sinn; Kulkeaw, Kasem; Nakanishi, Yoichi; Sugiyama, Daisuke
Abstract : In mouse fetal liver, hepatoblasts, sinusoidal endothelial cells and macrophages (or erythroblastic islands) promote differentiation and proliferation of hematopoietic cells through cell–cell interactions and secretion of cytokines and extracellular matrix factors. Until now, we have had little knowledge of the hematopoietic cytokines or extracellular matrix mRNAs expressed in hepatic stellate cells. Using p75 neurotrophin receptor (p75NTR) to mark this cell population, we sorted 12.5, 14.5 and 16.5 dpc hepatic stellate cells and analyzed expression of cytokines and extracellular matrix mRNAs. Among cytokines, insulin‐like growth factor 2 ( Igf2 ) was highly expressed at all three stages analyzed. The extracellular matrix molecule fibronectin ( Fn1 ) was highly expressed in 12.5 dpc cells, whereas vitronectin ( Vtn ) was highly expressed in 14.5 and 16.5 dpc hepatic stellate cells. Among liver cells, Igf2 was predominantly expressed in hepatoblast‐like cells at all three stages examined, suggesting that hepatoblast‐like cells are an essential part of the niche that maintains homeostasis of hematopoietic cells in embryonic mouse liver. Defining these expression patterns could facilitate our understanding of cross talk between cytokine and extracellular matrix molecules in hepatic stellate cells and benefit research in developmental hematopoiesis as well as the study of liver biology. Abstract : Embryonic hepatic stellate cells express hematopoietic niche factors. mRNA encoding the cytokine Igf2 is highly expressed in 12.5, 14.5 and 16.5 dpc mouse hepatic stellate cells. mRNA encoding the extracellular matrix factor Fn1 is highly expressed in 12.5 dpc hepatic stellate cells, while Vtn mRNA is highly expressed at 14.5 and 16.5 dpc. Igf2 mRNA is highly expressed in 12.5, 14.5 and 16.5 dpc hepatoblast‐like cells relative to other liver cells.